Biologically-Derived Nanomaterials for Targeted Therapeutic Delivery to the Brain. (September 2018) - Curley, Stephanie M.; Cady, Nathaniel C.
Delivery of imaging agents and pharmaceutical payloads to the central nervous system (CNS) is essential for efficient diagnosis and treatment of brain diseases. However, therapeutic delivery is often restricted by the blood-brain barrier (BBB), which prevents transport of clinical compounds to their region of interest. This review discusses the methods that have been used to avoid or overcome this barrier, presenting the use of biologically-derived nanomaterial systems as an efficient strategy for the diagnosis and treatment of CNS diseases. Biological nanomaterials have many advantages over synthetic systems, including being biodegradable, biocompatible, easily surface functionalised for conjugation of targeting moieties, and are often able to self-assemble. These abilities are discussed in relation to various systems, including liposomes, dendrimers, and viral nanoparticles.